1994
DOI: 10.1139/e94-015
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost, tectonics, and past and future regional climate change, Yukon and adjacent Northwest Territories

Abstract: Late Tertiary changes in the general circulation of the atmosphere, regionally enhanced by uplift of the Wrangell -Saint Elias and Coast mountains, were sufficient to promote permafrost development in the western Arctic. Permafrost developed in Yukon Territory and adjacent Northwest Territories during early Pleistocene glacial periods, after continued tectonic activity led to further modification of regional climate, but degraded in the interglacials. Permafrost has been present in northem parts of the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…Burn (1994) presented evidence for progressively increasing continentality in central and southern Yukon during the late Pliocene and Pleistocene. He concluded that widespread permafrost in southern and central Yukon is unique to the Holocene interglaciation.…”
Section: Discussionmentioning
confidence: 99%
“…Burn (1994) presented evidence for progressively increasing continentality in central and southern Yukon during the late Pliocene and Pleistocene. He concluded that widespread permafrost in southern and central Yukon is unique to the Holocene interglaciation.…”
Section: Discussionmentioning
confidence: 99%
“…Scenario temperature changes in this paper are indicated in degrees Kelvin (K) in order to avoid confusion with MAATs which are stated in degrees Celsius. A scenario approach was favoured over applying global or regional climate model predictions which suffer from inadequate representation of the topography in the Yukon (see Burn, 1994). Permafrost conditions were also investigated under a cooler MAAT (−1 K) that may be representative of conditions during the Little Ice Age (LIA; Farnell et al, 2004).…”
Section: Regional Model Perturbation For Climate Change Scenariosmentioning
confidence: 99%
“…We investigated a Lewkowicz and Bonnaventure (2008) because values in the PISR field are corrected from those generated before the error in the Solar Analyst software was discovered (see text) range of warming values up to +5 K based on IPCC and ACIA predictions for the upcoming century. We chose this approach rather than using Global or Regional Climate Model predictions because of the problem of adequately representing the topography in the western Cordillera where our sites are located (see Burn 1994).…”
Section: Climate Change Scenario Modellingmentioning
confidence: 99%